the Effect of One-Way Street Policy Towards the Income of MSME Sector - Ayu, Lely Kusumaning; Soesilowati, Etty (Universitas Negeri Semarang, 2019)
The aims of this study was to analyze the effect of implementation of one-way street policy towards the income and to find out how the MSME (Micro, Small and Medium Enterprise) strategy in MH Thamrin-Gajah Mada street. The method that was used in this research was percentage description, with data analysis tools Paired Samples T-Test and SWOT analysis. Data is collected through observation, interviews and documentation. The results of this study showed that (1) the value of paired t test for the average income of business actor in goods sector has decreased by 34%, then for service businesses has decreased by 40%. (2) The results of SWOT analysis explained that the direction strategy of MSME sector development was in growth and development phase with IFE (Internal Factor Evaluation) scores = 2.86 and EFE (External Factor Evaluation) = 3.07, so the development strategy of MSME sector is development business in another place, business coaching by related agencies, business innovation, creating promotions by using social media, training, maintaining product selling prices, and coordination between agencies related to the business actor. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh penerapan kebijakan satu arah jalan terhadap pendapatan dan untuk mengetahui bagaimana strategi UMKM (Usaha Mikro, Kecil dan Menengah) di jalan MH Thamrin-Gajah Mada. Metode yang digunakan dalam penelitian ini adalah deskripsi persentase, dengan alat analisis data Paired Samples T-Test dan analisis SWOT. Data dikumpulkan melalui observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa (1) nilai paired t test untuk pendapatan rata-rata pelaku usaha di sektor barang mengalami penurunan sebesar 34%, maka untuk bisnis jasa mengalami penurunan sebesar 40%. (2) Hasil analisis SWOT menjelaskan bahwa arah strategi pengembangan sektor UMKM adalah pada fase pertumbuhan dan perkembangan dengan skor IFE (Evaluasi Faktor Internal) = 2,86 dan EFE (Evaluasi Faktor Eksternal) = 3,07, sehingga strategi pengembangan sektor UMKM adalah pengembangan bisnis di tempat lain, pembinaan bisnis oleh agen terkait, inovasi bisnis, membuat promosi dengan menggunakan media sosial, pelatihan, menjaga harga jual produk, dan koordinasi antara agen terkait dengan pelaku bisnis.